Negative electrode material and preparation method thereof, negative electrode sheet and battery
By heat treatment of hard carbon precursors and cross-polymerization of nitrogen source compounds and combined with carbon coating treatment, the problem of reversible capacity and low Coulomb efficiency of hard carbon materials in the battery is solved, efficient preparation of negative electrode materials is achieved, and the battery is improved performance.
Patent Information
- Application Number
- CN202411155170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Hard carbon materials have problems with low reversible capacity and low first-time Coulomb efficiency in battery applications, which cannot meet the needs of power batteries.
By performing a first heat treatment on the hard carbon precursor, the specific surface area and the number of pores are increased, followed by cross-linking polymerization with the nitrogen source compound, and carbon coating treatment is performed to modify the surface defects to form an efficient negative electrode material.
It significantly improves the capacity performance and first-time Coulomb efficiency of the negative electrode material, improves the diffusion rate and storage capacity of sodium ions, and meets the needs of power batteries.
Smart Images

Figure CN118684212B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] With the rapid development of electric vehicles, portable electronic devices and large-scale electrochemical energy storage power stations, lithium-ion batteries and sodium-ion batteries, as electrochemical energy storage devices, have become the focus of attention in the new energy industry. The selection and optimization of positive and negative electrode materials of batteries play a key role in the energy density, power density, safety and cost of battery systems. Hard carbon materials are abundant in sources and low in cost. As a new type of negative electrode material, it has higher lithium storage capacity and rate performance than the graphite negative electrode of lithium-ion batteries, and is the negative electrode material with the most market potential for sodium-ion batteries.
[0003] The hard carbon precursor part determines the performance of hard carbon materials. Precursors are divided into fossil fuel-based, resin-based and biomass-based. Fossil fuel-based precursors are widely available, have high carbon yields, and have an advantage in raw material cost. However, direct carbonization easily results in soft carbon. When preparing fossil fuel-based hard carbon, it is necessary to pre-oxidize before carbonization. The current process is not mature enough, and the gram capacity of the obtained hard carbon material is low. Resin-based hard carbon has excellent performance and good consistency. It can finely control the pore structure, surface chemical properties and active sites, but due to its high cost, its current application progress is slow. Biomass-based precursors have unique microstructures, and they have the advantages of self-doping effects, multiple active sites, low costs, and a wide range of sources. They are the preferred precursor raw materials after the industrialization of sodium-ion batteries. However, in practical applications, hard carbon materials still have some problems, such as low reversible capacity, which cannot meet the needs of current power battery applications, and low first coulomb efficiency (first efficiency). Summary of the invention
[0004] In view of this, the embodiments of the present application provide a negative electrode material and a preparation method thereof, a negative electrode plate and a battery to solve at least one problem existing in the background technology.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing a negative electrode material, the method comprising the following steps:
[0006] S1: Under a first inert gas atmosphere, performing a first heat treatment on a hard carbon precursor to obtain a first precursor, wherein the hard carbon precursor includes an oxygen-containing functional group;
[0007] S2: adding the first precursor, the nitrogen source compound, the crosslinking agent and the initiator into a solvent to carry out a crosslinking polymerization reaction, filtering, washing and drying to obtain a second precursor; the mass ratio of the first precursor, the nitrogen source compound, the crosslinking agent and the initiator is 100: (0.1-5): (0.1-2): (0.1-2);
[0008] S3: performing carbon coating treatment on the second precursor to obtain the negative electrode material.
[0009] In conjunction with the first aspect of the present application, in an optional implementation manner, step S1 satisfies at least one of the following features (1) to (6):
[0010] (1) The first inert gas includes at least one of argon, nitrogen, and helium;
[0011] (2) The hard carbon precursor includes at least one of sodium alginate, starch, β-cyclodextrin, glucose, fructose, cellulose, and lignin;
[0012] (3) The oxygen-containing functional groups include carboxyl and / or hydroxyl groups;
[0013] (4) The temperature of the first heat treatment is 200°C to 600°C;
[0014] (5) The heating rate of the first heat treatment is 0.1°C / min~10°C / min, and the holding time is 0.5h~6h;
[0015] (6) The specific surface area of the first precursor is 100 m 2 / g~300m 2 / g.
[0016] In conjunction with the first aspect of the present application, in an optional implementation manner, step S2 satisfies at least one of the following features (1) to (5):
[0017] (1) The nitrogen source compound includes at least one of acrylamide, urea, hydrazine hydrate, pyrrole nitrogen, pyridine nitrogen, and acrylonitrile;
[0018] (2) The cross-linking agent includes at least one of tetramethylethylenediamine, N,N'-methylenebisacrylamide, and ethylene glycol dimethacrylate;
[0019] (3) The initiator includes at least one of azobisisobutyl cyanide, ammonium persulfate-sodium bisulfite, azobisisobutyl cyanide, and hydrogen peroxide;
[0020] (4) The solvent includes at least one of water, ethanol, acetone, toluene, ether, N,N'-dimethylformamide, and ethylene glycol monomethyl ether;
[0021] (5) The temperature of the cross-linking polymerization reaction is 80°C to 150°C.
[0022] In conjunction with the first aspect of the present application, in an optional implementation manner, the carbon coating treatment in step S3 includes:
[0023] A carbon source gas is introduced to perform gas phase coating on the second precursor; the gas phase coating has at least one of the following characteristics: a) the gas phase deposition temperature is 600°C~1000°C; b) the deposition time is 2h~5h; c) the introduction flow rate of the carbon source gas is 2L / min~10L / min; d) the carbon source gas includes alkane and / or alkene compounds.
[0024] In conjunction with the first aspect of the present application, in an optional implementation manner, before step S1, the method further includes:
[0025] The hard carbon precursor is purified by an acid solution, then washed with water to a pH of 5-8, and filtered and dried to obtain a purified hard carbon precursor; the purification process has at least one of the following characteristics: a) the mass fraction of the acid solution is 1%-18%; b) the acid solution includes at least one of sulfuric acid, nitric acid, hydrofluoric acid, and hydrochloric acid; c) the ash content of the purified hard carbon precursor is ≤2%; d) the median particle size Dv50 of the purified hard carbon precursor is 2μm-6μm.
[0026] In conjunction with the first aspect of the present application, in an optional implementation manner, the method further includes:
[0027] Under a second inert gas atmosphere, the negative electrode material is subjected to a second heat treatment, and the second heat treatment has at least one of the following characteristics: a) the temperature of the second heat treatment is 1000°C~1600°C; b) the insulation time is 2h~5h; c) the heating rate is 1°C / min~5°C / min; d) the second inert gas includes at least one of argon, nitrogen, and helium.
[0028] In conjunction with the first aspect of the present application, in an optional implementation manner, the method further includes:
[0029] After the second heat treatment, cooling and sieving are performed; the negative electrode material after sieving has at least one of the following characteristics: a) ash content ≤ 0.05%; b) median particle size Dv50 is 4 μm~8 μm; c) specific surface area is 5m 2 / g~15m 2 / g.
[0030] In a second aspect, an embodiment of the present application provides a negative electrode material, which is prepared using the method for preparing a negative electrode material as described in any one of the first aspects.
[0031] In a third aspect, an embodiment of the present application provides a negative electrode plate, which includes a negative electrode material prepared by the preparation method described in any one of the first aspects or includes the negative electrode material described in the second aspect.
[0032] In a fourth aspect, an embodiment of the present application provides a battery, comprising the negative electrode plate as described in the third aspect.
[0033] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0034] The negative electrode material and its preparation method, negative electrode plate and battery provided in the embodiments of the present application, firstly, by performing a first heat treatment on the hard carbon precursor, excess ash and volatile matter in the material can be removed, and at the same time, organic and inorganic small molecules escape from the surface of the material, thereby increasing the surface defects, the number of pores and the pore volume of the first precursor, so that the specific surface area of the first precursor is significantly increased, which can provide sufficient space for the doping of nitrogen source compounds; secondly, the nitrogen source compound forms free radicals with positive charge under the action of the initiator, and chemically cross-links with oxygen-containing functional groups at the defects of the first precursor and between the intercalations, so as to achieve sufficient and precise doping of the nitrogen source compound, provide a large number of adsorption active sites for active ions, expand the distance between graphite layers, and thus effectively improve the diffusion rate of active ions; thirdly, carbon coating treatment of the second precursor can modify the surface defects of the second precursor, thereby improving the capacity performance and the first coulombic efficiency of the negative electrode material.
[0035] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0037] Figure 1 A schematic diagram of a process for preparing a negative electrode material provided in an embodiment of the present application;
[0038] Figure 2 This is a scanning electron microscope image of the negative electrode material prepared in Example 1;
[0039] Figure 3 This is a transmission electron microscope image of the negative electrode material prepared in Example 1;
[0040] Figure 4 The charge and discharge curve of the battery made of the negative electrode material prepared in Example 1;
[0041] Figure 5The charge and discharge curve of the battery made of the negative electrode material prepared in Comparative Example 1;
[0042] Figure 6 The charge and discharge curve of the battery made of the negative electrode material prepared in Comparative Example 2;
[0043] Figure 7 This is the charge and discharge curve of the battery made of the negative electrode material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0044] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0045] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0046] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0047] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0048] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0049] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0050] In the related technology, the main means to improve the sodium storage performance of hard carbon materials is to regulate the synthesis and pyrolysis process parameters of the precursor (such as carbonization temperature, purge gas flow rate, and heating rate) to microscopically regulate the porosity of the hard carbon materials. In addition, heteroatom doping is a method to improve the physical and chemical properties and structural properties of hard carbon materials. Heteroatom doping changes the local structure of the hard carbon material, resulting in an increase in the interlayer spacing of the carbon layer, an increase in the volume of the micropores, and the generation of defect sites, thereby generating more adsorbed active ions (such as Na + or Li + ) active sites, which reduces the diffusion barrier, increases the conductivity of the material, and improves the reversible capacity. However, heteroatom doping also brings about uncontrollable proportion of defective sites, resulting in problems such as low first efficiency of the battery.
[0051] Based on this, the present application embodiment provides a method for preparing a negative electrode material. Figure 1 The method for preparing the modified positive electrode material provided in the embodiment of the present application comprises the following steps:
[0052] S1: Under a first inert gas atmosphere, performing a first heat treatment on a hard carbon precursor to obtain a first precursor, wherein the hard carbon precursor includes an oxygen-containing functional group;
[0053] S2: adding the first precursor, the nitrogen source compound, the crosslinking agent and the initiator into a solvent to carry out a crosslinking polymerization reaction, filtering, washing and drying to obtain a second precursor; the mass ratio of the first precursor, the nitrogen source compound, the crosslinking agent and the initiator is 100: (0.1~5): (0.1~2): (0.1~2);
[0054] S3: performing carbon coating treatment on the second precursor to obtain a negative electrode material.
[0055] In the embodiment of the present application, firstly, the excess ash and volatile matter in the material can be removed by performing a first heat treatment on the hard carbon precursor, and at the same time, small organic and inorganic molecules escape from the surface of the material, increasing the surface defects, the number of pores and the pore volume of the first precursor, so that the specific surface area of the first precursor is significantly increased, which can provide sufficient space for the doping of the nitrogen source compound. Secondly, the nitrogen source compound forms a free radical with a positive charge under the action of the initiator, and chemically cross-links with the oxygen-containing functional groups at the defects of the first precursor and between the intercalations, so as to achieve sufficient and precise doping of the nitrogen source compound, which can be used for active ions (such as Na + or Li +) provides a large number of adsorption active sites, expands the distance between graphite layers, and thus effectively improves the diffusion rate of active ions. Furthermore, carbon coating of the second precursor can modify the surface defects of the second precursor, thereby improving the capacity performance and first coulombic efficiency of the negative electrode material.
[0056] In the embodiment of the present application, the mass ratio of the first precursor, the nitrogen source compound, the cross-linking agent and the initiator is controlled to be 100: (0.1~5): (0.1~2): (0.1~2), for example, it can be (100:2:0.1:0.1), (100:1.5:0.5:0.2), (100:1:0.5:0.2) or any other mass ratio range within the above range. Through cross-linking polymerization reaction, the nitrogen source compound and the oxygen-containing functional groups in the carbon skeleton can be cross-linked by chemical bonds to form a large number of sites at the surface defects of the hard carbon precursor and in the intercalation layer, while expanding the interlayer spacing to increase the capacity performance of the negative electrode material. In this way, it is conducive to the preparation of high-quality negative electrode materials.
[0057] In some embodiments, the oxygen-containing functional groups included in the hard carbon precursor may be carboxyl groups and / or hydroxyl groups, which can undergo a good cross-linking reaction with the nitrogen source compound, so that nitrogen can be accurately doped into the first precursor in the subsequent step S2.
[0058] In some embodiments, the hard carbon precursor may include a biomass-based hard carbon material, because the biomass-based hard carbon material has a unique microstructure, has advantages such as self-doping effect, many active sites, low cost, and a wide range of sources. Specifically, the hard carbon precursor may include at least one of sodium alginate, starch, β-cyclodextrin, glucose, fructose, cellulose, and lignin. The above-mentioned biomass-based hard carbon materials contain rich oxygen-containing groups, such as carboxyl and / or hydroxyl functional groups, so that the first precursor can undergo sufficient cross-linking reaction with the nitrogen source compound, thereby achieving better nitrogen doping to further enhance the sodium storage performance of the negative electrode material. In practical applications, the biomass-based hard carbon precursor can be first ball-milled and then sieved through a 50-mesh to 500-mesh sieve to obtain a hard carbon precursor.
[0059] In some embodiments, before executing step S1, the method for preparing the negative electrode material may further include: purifying the hard carbon precursor with an acid solution, then washing with water to a pH of 5 to 8, and obtaining a purified hard carbon precursor by filtering and drying.
[0060] In the embodiment of the present application, the hard carbon precursor is purified by an acid solution to remove excess inorganic impurities in the hard carbon precursor raw material. At the same time, the acid solution can also act as an oxidant to increase the oxygen-containing functional groups in the carbon skeleton of the hard carbon precursor, thereby promoting the cross-linking polymerization reaction in the subsequent step S2.
[0061] Exemplarily, the mass fraction of the acid solution may be 1%-18%, for example, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18% or any value between any two of the above numerical ranges, and the acid solution may include, for example, at least one of sulfuric acid, nitric acid, hydrofluoric acid, and hydrochloric acid. Specifically, those skilled in the art may dilute the concentrated acid solution according to actual needs to obtain an acid solution with a desired mass fraction.
[0062] In some embodiments, the ash content of the purified hard carbon precursor is ≤ 2%. In this way, by reducing the impurities in the hard carbon precursor raw material, the performance of the final negative electrode material can be improved.
[0063] In some embodiments, the median particle size Dv50 of the purified hard carbon precursor is 2 μm to 6 μm. By controlling the median particle size of the hard carbon precursor within the above range, a high-quality negative electrode material can be prepared.
[0064] In some embodiments, the first inert gas in step S1 may include at least one of argon, nitrogen, and helium, which is used to protect the hard carbon precursor from being oxidized during the first heat treatment.
[0065] When the temperature of the first heat treatment in step S1 is low, the surface defects, pore quantity and pore volume of the first precursor cannot be effectively increased, and thus the specific surface area of the first precursor cannot be effectively increased. When the temperature of the first heat treatment is high, it is easy to make the short-range ordered graphite-like crystallites in the internal structure of the hard carbon material gradually grow, thereby causing the pores to gradually shrink, and then causing the specific surface area of the first precursor to decrease. Therefore, in some embodiments, the temperature of the first heat treatment is 200°C~600°C, for example, it can be 200°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or any value between any two of the above numerical ranges, so that the specific surface area of the first precursor can be effectively increased, thereby providing sufficient space for the doping of the nitrogen source compound in the subsequent step S2, so that nitrogen can be fully and accurately doped in the first precursor.
[0066] The heating rate and holding time of the first heat treatment are closely related to the effect of the first heat treatment. Therefore, in some embodiments, the heating rate of the first heat treatment can be 0.1°C / min~10°C / min, for example, 0.1°C / min, 1°C / min, 1.5°C / min, 3°C / min, 5°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between any two of the above numerical ranges, and the holding time of the first heat treatment can be 0.5h~6h, for example, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h or any value between any two of the above numerical ranges. Controlling the heating rate and holding time within the above range can obtain a first precursor with a suitable specific surface area after treating the hard carbon precursor, thereby providing better conditions for doping the nitrogen source compound in the subsequent step S2, so as to further improve the performance of the obtained negative electrode material.
[0067] In some embodiments, the specific surface area of the first precursor can be 100 m 2 / g~300m 2 / g, for example, 100m 2 / g, 120m 2 / g, 150m 2 / g, 180m 2 / g, 200m 2 / g, 230m 2 / g, 250m 2 / g, 280m 2 / g、300m 2 / g or any value between any two numerical ranges mentioned above. In this way, nitrogen can be more fully and accurately doped in the first precursor.
[0068] Specifically, when executing step S2, the first precursor, nitrogen source compound, cross-linking agent and initiator can be added to a stirring tank filled with a solvent in a mass ratio of 100: (0.1~5): (0.1~2): (0.1~2) in sequence and mixed evenly, and then transferred to a hydrothermal reactor and stirred and heated to perform a cross-linking polymerization reaction. After the reaction is complete, it is cooled to room temperature and filtered, washed and dried to obtain a second precursor.
[0069] There is no particular limitation on the types of the nitrogen source compound, cross-linking agent, initiator and solvent in step S2, and they can be selected according to actual needs.
[0070] The "nitrogen source compound" refers to a compound for providing nitrogen. For example, the nitrogen source compound may include at least one of acrylamide, urea, hydrazine hydrate, pyrrole nitrogen, pyridine nitrogen, and acrylonitrile.
[0071] The cross-linking agent is known to those skilled in the art as long as it can achieve a cross-linking reaction. For example, the cross-linking agent may include at least one of tetramethylethylenediamine, N,N'-methylenebisacrylamide, and ethylene glycol dimethacrylate.
[0072] The initiator is known to those skilled in the art as long as it can achieve the initiation reaction. For example, the initiator may include at least one of azobisisobutyl cyanide, ammonium persulfate-sodium bisulfite, azobisisobutyl cyanide, and hydrogen peroxide.
[0073] Illustratively, the solvent may include at least one of water, ethanol, acetone, toluene, diethyl ether, N,N'-dimethylformamide, and ethylene glycol monomethyl ether.
[0074] In some embodiments, the temperature of the cross-linking polymerization reaction in step S2 is 80° C. to 150° C. Within the above temperature range, the first precursor and the nitrogen source compound can be polymerized quickly, uniformly, and fully under the action of the cross-linking agent and the initiator, thereby achieving a better nitrogen doping effect, thereby further improving the capacity performance of the negative electrode material.
[0075] The filtering, washing and drying in the above step S2 can be performed by methods well known to those skilled in the art, which will not be described in detail here.
[0076] In some embodiments, the carbon coating treatment in the above step S3 may include: introducing a carbon source gas to perform gas-phase coating on the second precursor. Through gas-phase coating, carbon can be deposited on the interface of the second precursor, thereby modifying the surface defects of the second precursor, and obtaining a negative electrode material with a carbon coating layer, thereby improving the first coulombic efficiency.
[0077] The carbon source gas may include alkane and / or olefin compounds, and specifically, the carbon source gas may include at least one of methane, ethane, ethylene, and acetylene. By chemical vapor deposition, gas-phase small molecule alkane or olefin compounds are cracked so that they can be uniformly deposited on the interface of the hard carbon precursor, modifying the defects on the hard carbon surface, thereby better improving the first coulomb efficiency.
[0078] Specifically, the second precursor can be added into a vapor deposition furnace for vapor coating, for example, the temperature is increased from room temperature to a set vapor deposition temperature at a heating rate of 2°C / min to 5°C / min. During the heating process, nitrogen is introduced at a flow rate of 1L / min to 5L / min. After reaching the set temperature, a carbon source gas is introduced for vapor coating.
[0079] In some specific embodiments, the vapor deposition temperature in the vapor coating may be 600°C to 1000°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any value between any two of the above ranges. In this way, the carbon source gas can be fully cracked to better modify the surface defects of the second precursor, so as to prepare a high-quality negative electrode material and further improve the first coulombic efficiency.
[0080] At the above vapor deposition temperature, in some specific embodiments, the vapor deposition time may be 2h to 5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or any value between any two of the above ranges. In this way, carbon can be more evenly and fully deposited on the interface of the second precursor, thereby further enhancing the modification effect on the surface defects of the second precursor.
[0081] At the above vapor deposition temperature and / or vapor deposition time, the flow rate of the carbon source gas can be 2L / min to 10L / min, for example, 2L / min, 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min, 10L / min or any value between any two of the above numerical ranges. In this way, sufficient carbon source supply can be guaranteed, so that the carbon coating layer formed in the negative electrode material is more uniform, and the performance of the obtained negative electrode material is better.
[0082] In some embodiments, the method for preparing the negative electrode material may further include: performing a second heat treatment on the negative electrode material under a second inert gas atmosphere.
[0083] In the embodiment of the present application, the negative electrode material is carbonized by the second heat treatment, which can induce the growth and winding of graphite-like crystallites to form more microporous structures, provide more storage space for sodium ions, improve the capacity performance of the negative electrode material, and further reduce surface defects, thereby further improving the performance of the negative electrode material.
[0084] Specifically, the negative electrode material can be placed in a high-temperature carbonization furnace, and under the protection of a second inert gas atmosphere, the temperature is raised from room temperature to a set temperature at a heating rate of 1°C / min to 5°C / min, and then a second heat treatment is performed. The second inert gas can include, for example, at least one of argon, nitrogen, and helium, which is used to better protect the negative electrode material from oxidation during the second heat treatment.
[0085] It can be understood that when the temperature of the second heat treatment is low, it is not possible to effectively form more microporous structures in the negative electrode material and reduce the surface defects of the negative electrode material, and thus the performance of the negative electrode material cannot be effectively improved. When the temperature of the second heat treatment is high, excessive growth of graphite-like crystallites easily leads to pore closure, which is not conducive to improving the capacity performance of the negative electrode material. Therefore, in some embodiments, the temperature of the second heat treatment can be 1000°C to 1600°C, for example, 1000°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C or any value between any two of the above numerical ranges. In this way, the capacity performance and the first coulombic efficiency of the negative electrode material can be better improved, and high-quality negative electrode materials can be prepared.
[0086] The heating rate and holding time of the second heat treatment are closely related to the effect of the second heat treatment. Therefore, in some embodiments, the heating rate of the second heat treatment can be 1°C / min~5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between any two of the above numerical ranges. The holding time of the second heat treatment can be 2h~5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or any value between any two of the above numerical ranges. Controlling the heating rate and holding time within the above range can further improve the quality of the prepared negative electrode material.
[0087] In some embodiments, the method for preparing the negative electrode material further comprises: cooling and sieving after the second heat treatment, so as to obtain a negative electrode material with suitable particle size and excellent performance.
[0088] In some specific embodiments, the ash content of the negative electrode material after screening is ≤0.05%, so that the purity of the negative electrode material is higher, thereby making the performance of the negative electrode material better.
[0089] In some specific embodiments, the median particle size Dv50 of the negative electrode material after sieving is 4 μm to 8 μm, so that the negative electrode material can exert better performance in the battery.
[0090] In some specific embodiments, the specific surface area of the negative electrode material after sieving is 5m 2 / g~15m 2 / g. This can make the negative electrode material perform better when used in batteries.
[0091] Based on this, an embodiment of the present application further provides a negative electrode material, which is prepared using the preparation method of the negative electrode material described in any of the above embodiments.
[0092] It should be understood that all the features and advantages of the method for preparing the negative electrode material described in the above embodiments are also applicable to the negative electrode material in the embodiments of the present application, and will not be described one by one here.
[0093] Based on this, an embodiment of the present application further provides a negative electrode plate, including a negative electrode material prepared by the method for preparing the negative electrode material described in any of the above embodiments or including the negative electrode material described in the above embodiments.
[0094] It should be understood that since the negative electrode plate in the embodiments of the present application includes the negative electrode material prepared by the preparation method of the negative electrode material described in any of the above embodiments or includes the negative electrode material described in the above embodiments, the beneficial effects of the negative electrode material described in any of the above embodiments are applicable to the negative electrode plate.
[0095] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer may include a negative electrode material prepared by the preparation method of the negative electrode material described in any of the above embodiments or include the negative electrode material described in the above embodiments.
[0096] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.
[0097] The present application has no particular restrictions on the preparation method of the negative electrode sheet, and any preparation method known in the art may be selected as long as the purpose of the present application can be achieved.
[0098] Based on this, an embodiment of the present application also provides a battery, comprising the negative electrode plate described in the above embodiment.
[0099] It should be understood that, since the battery in the embodiment of the present application includes the negative electrode plate described in the above embodiment, the beneficial effects of the negative electrode plate described in any of the above embodiments are applicable to the battery.
[0100] In some embodiments, the battery may be a secondary battery, and the secondary battery may be a lithium-ion secondary battery or a sodium-ion secondary battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0101] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples. Example 1
[0102] The preparation of the negative electrode material in this embodiment includes the following steps:
[0103] S101: taking a certain amount of sodium alginate hard carbon precursor, ball milling and sieving, taking the sieve material for purification in a 10% sulfuric acid solution by mass fraction, washing with water to pH=6, filtering and drying, and obtaining a sodium alginate hard carbon precursor powder with an ash content of 2% and a median particle size of 4.18 μm;
[0104] S102: Under the protection of N2 atmosphere, the purified sodium alginate hard carbon precursor powder obtained in step S101 is placed in a carbonization furnace for low-temperature pretreatment (first heat treatment). The temperature of the low-temperature pretreatment is 200°C, the heating rate is 2°C / min, and the insulation time is 2h to obtain a first precursor. The specific surface area of the first precursor is 150m 2 / g;
[0105] S103: the first precursor obtained in step S102 is added to a stirring kettle filled with ethanol solvent in a mass ratio of 100:2:0.1:0.1 in sequence and mixed evenly, and then transferred to a reaction kettle for heating and stirring to perform a cross-linking polymerization reaction at a heating temperature of 80° C. until the system reacts completely, and then cooled to room temperature, and filtered, washed and dried to obtain a second precursor;
[0106] S104: adding the second precursor obtained in step S103 into a vapor deposition furnace, performing vapor coating under N2 atmosphere protection, the flow rate of N2 is 3 L / min, the temperature is increased from room temperature to 800°C at a heating rate of 2°C / min, when the vapor deposition furnace reaches the deposition temperature of 800°C, starting to introduce carbon source gas at a flow rate of 3 L / min for vapor deposition, the deposition time is 2 hours, and cooling to room temperature to obtain the negative electrode material;
[0107] S105: The negative electrode material obtained in step S104 is placed in a high-temperature carbonization furnace and subjected to high-temperature carbonization (second heat treatment) under the protection of N2 atmosphere. The carbonization temperature is raised from room temperature to 1200°C at a heating rate of 1.5°C / min, and the insulation time is 2h. After the insulation is completed, it is cooled to room temperature and sieved through 300 mesh to obtain a ash content of 0.05%, a median particle size of 6.35μm, and a specific surface area of 4.39m 2 / g of negative electrode material. Example 2
[0108] The preparation of the negative electrode material in this embodiment includes the following steps:
[0109] S101: taking a certain amount of starch hard carbon precursor, ball milling and sieving, taking the sieve material for purification in a sulfuric acid solution with a mass fraction of 18%, washing with water to pH=7, filtering and drying, and obtaining a starch hard carbon precursor powder with an ash content of 1.5% and a median particle size of 6.18 μm;
[0110] S102: Under the protection of N2 atmosphere, the purified starch hard carbon precursor powder obtained in step S101 is placed in a carbonization furnace for low-temperature pretreatment (first heat treatment). The temperature of the low-temperature pretreatment is 300°C, the heating rate is 2°C / min, and the insulation time is 2h to obtain a first precursor. The specific surface area of the first precursor is 125m 2 / g;
[0111] S103: the first precursor obtained in step S102 is added to a stirring kettle filled with acetone solvent in a mass ratio of 100:1.5:0.5:0.2 in sequence and mixed evenly, and then transferred to a reaction kettle for heating and stirring to perform a cross-linking polymerization reaction at a heating temperature of 85° C. until the system reacts completely, and then cooled to room temperature, and filtered, washed and dried to obtain a second precursor;
[0112] S104: adding the second precursor obtained in step S103 into a vapor deposition furnace, performing vapor coating under N2 atmosphere protection, the flow rate of N2 is 2.5 L / min, the temperature is increased from room temperature to 1000°C at a heating rate of 3°C / min, when the vapor deposition furnace reaches the deposition temperature of 1000°C, starting to introduce carbon source gas at a flow rate of 2.5 L / min for vapor deposition, the deposition time is 2 hours, and cooling to room temperature to obtain the negative electrode material;
[0113] S105: The negative electrode material obtained in step S104 is placed in a high-temperature carbonization furnace and subjected to high-temperature carbonization (second heat treatment) under the protection of N2 atmosphere. The carbonization temperature is raised from room temperature to 1400°C at a heating rate of 2°C / min, and the insulation time is 3h. After the insulation is completed, it is cooled to room temperature and sieved through 300 mesh to obtain a ash content of 0.01%, a median particle size of 7.35μm, and a specific surface area of 5.78m 2 / g of negative electrode material. Example 3
[0114] The preparation of the negative electrode material in this embodiment includes the following steps:
[0115] S101: taking a certain amount of sodium alginate hard carbon precursor, ball milling and sieving, taking the sieve material for purification in a nitric acid solution with a mass fraction of 1%, washing with water to pH=7, filtering and drying, and obtaining a sodium alginate hard carbon precursor powder with an ash content of 1.2% and a median particle size of 5.28 μm;
[0116] S102: Under the protection of N2 atmosphere, the purified sodium alginate hard carbon precursor powder obtained in step S101 is placed in a carbonization furnace for low-temperature pretreatment (first heat treatment). The temperature of the low-temperature pretreatment is 400°C, the heating rate is 1.5°C / min, and the insulation time is 3h to obtain a first precursor. The specific surface area of the first precursor is 175m 2 / g;
[0117] S103: the first precursor obtained in step S102 is added to a stirring kettle filled with acetone solvent in a mass ratio of 100:1:0.5:0.2 in sequence and mixed evenly, and then transferred to a reaction kettle for heating and stirring to perform a cross-linking polymerization reaction at a heating temperature of 90° C. until the system reacts completely, and then cooled to room temperature, and filtered, washed and dried to obtain a second precursor;
[0118] S104: adding the second precursor obtained in step S103 into a vapor deposition furnace, performing vapor coating under N2 atmosphere protection, the flow rate of N2 is 2 L / min, the temperature is increased from room temperature to 800°C at a heating rate of 2°C / min, when the vapor deposition furnace reaches the deposition temperature of 800°C, starting to introduce carbon source gas at a flow rate of 4 L / min for vapor deposition, the deposition time is 4 hours, and cooling to room temperature to obtain the negative electrode material;
[0119] S105: The negative electrode material obtained in step S104 is placed in a high-temperature carbonization furnace and subjected to high-temperature carbonization (second heat treatment) under the protection of N2 atmosphere. The carbonization temperature is raised from room temperature to 1350°C at a heating rate of 1.8°C / min, and the insulation time is 2h. After the insulation is completed, it is cooled to room temperature and sieved through 300 mesh to obtain a ash content of 0.12%, a median particle size of 5.55μm, and a specific surface area of 6.24m 2 / g of negative electrode material. Example 4
[0120] The preparation of the negative electrode material in this embodiment includes the following steps:
[0121] S101: taking a certain amount of glucose hard carbon precursor, ball milling and sieving, taking the sieve material for purification in a nitric acid solution with a mass fraction of 15%, washing with water to pH=7, filtering and drying, and obtaining a glucose hard carbon precursor powder with an ash content of 1.2% and a median particle size of 5.58 μm;
[0122] S102: Under the protection of N2 atmosphere, the purified glucose hard carbon precursor powder obtained in step S101 is placed in a carbonization furnace for low-temperature pretreatment (first heat treatment). The temperature of the low-temperature pretreatment is 400°C, the heating rate is 1.5°C / min, and the insulation time is 3h to obtain a first precursor. The specific surface area of the first precursor is 105m 2 / g;
[0123] S103: the first precursor obtained in step S102 is added to a stirring kettle filled with acetone solvent in a mass ratio of 100:1:0.5:0.2 in sequence and mixed evenly, and then transferred to a reaction kettle for heating and stirring to perform a cross-linking polymerization reaction at a heating temperature of 90° C. until the system reacts completely, and then cooled to room temperature, and filtered, washed and dried to obtain a second precursor;
[0124] S104: adding the second precursor obtained in step S103 into a vapor deposition furnace, performing vapor coating under N2 atmosphere protection, the flow rate of N2 is 2 L / min, the temperature is increased from room temperature to 800°C at a heating rate of 2°C / min, when the vapor deposition furnace reaches the deposition temperature of 800°C, starting to introduce carbon source gas at a flow rate of 4 L / min for vapor deposition, the deposition time is 4 hours, and cooling to room temperature to obtain the negative electrode material;
[0125] S105: The negative electrode material obtained in step S104 is placed in a high-temperature carbonization furnace and subjected to high-temperature carbonization (second heat treatment) under the protection of N2 atmosphere. The carbonization temperature is raised from room temperature to 1350°C at a heating rate of 1.8°C / min, and the insulation time is 2h. After the insulation is completed, it is cooled to room temperature and sieved through 300 mesh to obtain a ash content of 0.12%, a median particle size of 5.28μm, and a specific surface area of 4.99m 2 / g of negative electrode material.
[0126] Comparative Example 1
[0127] The preparation of the negative electrode material in this comparative example includes the following steps:
[0128] S101: taking a certain amount of sodium alginate hard carbon precursor, ball milling and sieving, taking the sieve material for purification in a 10% sulfuric acid solution by mass fraction, washing with water to pH=6, filtering and drying, and obtaining a sodium alginate hard carbon precursor powder with an ash content of 2% and a median particle size of 4.18 μm;
[0129] S103: The sodium alginate hard carbon precursor powder obtained in step S101 is added to a stirring kettle filled with ethanol solvent in a mass ratio of 100:2:0.1:0.1 in sequence and mixed evenly, and then transferred to a reaction kettle for heating and stirring to perform a cross-linking polymerization reaction at a heating temperature of 80° C. until the system reacts completely and then cooled to room temperature, and filtered, washed and dried to obtain a second precursor;
[0130] S104: adding the second precursor obtained in step S103 into a vapor deposition furnace, performing vapor coating under N2 atmosphere protection, the flow rate of N2 is 3 L / min, the temperature is increased from room temperature to 800°C at a heating rate of 2°C / min, when the vapor deposition furnace reaches the deposition temperature of 800°C, starting to introduce carbon source gas at a flow rate of 3 L / min for vapor deposition, the deposition time is 2 hours, and cooling to room temperature to obtain the negative electrode material;
[0131] S105: The negative electrode material obtained in step S104 is placed in a high-temperature carbonization furnace and subjected to high-temperature carbonization (second heat treatment) under the protection of N2 atmosphere. The carbonization temperature is raised from room temperature to 1200°C at a heating rate of 1.5°C / min, and the insulation time is 2h. After the insulation is completed, it is cooled to room temperature and sieved through 300 mesh to obtain a ash content of 0.05%, a median particle size of 5.96μm, and a specific surface area of 5.66m 2 / g of negative electrode material.
[0132] Comparative Example 2
[0133] The preparation of the negative electrode material in this comparative example includes the following steps:
[0134] S101: taking a certain amount of sodium alginate hard carbon precursor, ball milling and sieving, taking the sieve material for purification in a 10% sulfuric acid solution by mass fraction, washing with water to pH=6, filtering and drying, and obtaining a sodium alginate hard carbon precursor powder with an ash content of 2% and a median particle size of 4.18 μm;
[0135] S102: Under the protection of N2 atmosphere, the purified sodium alginate hard carbon precursor powder obtained in step S101 is placed in a carbonization furnace for low-temperature pretreatment (first heat treatment). The temperature of the low-temperature pretreatment is 200°C, the heating rate is 2°C / min, and the insulation time is 2h to obtain a first precursor. The specific surface area of the first precursor is 150m 2 / g;
[0136] S103: the first precursor obtained in step S102 is added to a stirring kettle filled with ethanol solvent in a mass ratio of 100:2:0.1:0.1 in sequence and mixed evenly, and then transferred to a reaction kettle for heating and stirring to perform a cross-linking polymerization reaction at a heating temperature of 80° C. until the system reacts completely, and then cooled to room temperature, and filtered, washed and dried to obtain a second precursor;
[0137] S105: The second precursor obtained in step S103 is placed in a high-temperature carbonization furnace and subjected to high-temperature carbonization (second heat treatment) under the protection of N2 atmosphere. The carbonization temperature is raised from room temperature to 1200°C at a heating rate of 1.5°C / min, and the insulation time is 2h. After the insulation is completed, it is cooled to room temperature and sieved through 300 mesh to obtain a ash content of 0.05%, a median particle size of 5.11μm, and a specific surface area of 17.15m 2 / g of negative electrode material.
[0138] Comparative Example 3
[0139] The preparation of the negative electrode material in this comparative example includes the following steps:
[0140] S101: taking a certain amount of sodium alginate hard carbon precursor, ball milling and sieving, taking the sieve material for purification in a 10% sulfuric acid solution by mass fraction, washing with water to pH=6, filtering and drying, and obtaining a sodium alginate hard carbon precursor powder with an ash content of 2% and a median particle size of 4.18 μm;
[0141] S102: Under the protection of N2 atmosphere, the purified sodium alginate hard carbon precursor powder obtained in step S101 is placed in a carbonization furnace for low-temperature pretreatment (first heat treatment). The temperature of the low-temperature pretreatment is 200°C, the heating rate is 2°C / min, and the insulation time is 2h to obtain a first precursor. The specific surface area of the first precursor is 150m 2 / g;
[0142] S104: adding the first precursor obtained in step S102 into a vapor deposition furnace, performing vapor coating under N2 atmosphere protection, the flow rate of N2 is 3 L / min, the temperature is increased from room temperature to 800°C at a heating rate of 2°C / min, when the vapor deposition furnace reaches the deposition temperature of 800°C, starting to introduce carbon source gas at a flow rate of 3 L / min for vapor deposition, the deposition time is 2 hours, and cooling to room temperature to obtain the negative electrode material;
[0143] S105: The negative electrode material obtained in step S104 is placed in a high-temperature carbonization furnace and subjected to high-temperature carbonization (second heat treatment) under the protection of N2 atmosphere. The carbonization temperature is raised from room temperature to 1200°C at a heating rate of 1.5°C / min, and the insulation time is 2h. After the insulation is completed, it is cooled to room temperature and sieved through 300 mesh to obtain a ash content of 0.05%, a median particle size of 6.49μm, and a specific surface area of 5.76m 2 / g of negative electrode material.
[0144] The negative electrode materials obtained in the above embodiments and comparative examples were assembled into half-cells to test the electrochemical performance of the battery. The specific operation steps are as follows: 19g of negative electrode material, 5.0g of conductive carbon black (super-P) and 5.0g of binder (2.5% sodium carboxymethyl cellulose) were weighed, and the slurry was mixed by magnetic stirring at a speed of 500rpm, and then coated on the current collector and placed in a vacuum oven at 80℃ for 8h to remove moisture to obtain a pole piece, with a sodium sheet as the counter electrode, a polypropylene microporous membrane as the diaphragm, and an electrolyte of 1M NaClO4 in a three-component mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and propylene carbonate (PC) in a volume ratio of 1:1:1 to obtain a battery to be tested.
[0145] The battery is tested to obtain the battery's first discharge specific capacity, first charge specific capacity and first coulombic efficiency.
[0146] 0.1C discharge capacity: Discharge at 0.1C constant current to 0V and let stand for 5 minutes. The capacity measured in this step is the 0.1C discharge capacity (denoted as C0), which is the first discharge specific capacity.
[0147] 0.1C charging capacity: 0.1C constant current and constant voltage charging to 2.0V, the cut-off current is 0.05C, and it is left to stand for 5 minutes. The capacity measured in this step is the 0.1C charging capacity (denoted as C1), which is the first charging specific capacity.
[0148] The first coulombic efficiency is: C1 / C0.
[0149] The test results are shown in Table 1.
[0150] It can be seen from the test results of Examples 1 to 4 and Comparative Examples 1 to 3 in Table 1 that, in the present application, the ash, volatile matter and moisture in the hard carbon precursor are removed by the first heat treatment. During the first heat treatment, the organic and inorganic small molecules in the hard carbon precursor escape from the surface of the material to form a porous structure, thereby increasing the specific surface area of the hard carbon precursor material, exposing more active sites, so that the nitrogen source compound can fully react with the oxygen-containing functional group for chemical cross-linking, thereby expanding the interlayer spacing d of the graphite carbon layer. 002, improve the sodium ion adsorption efficiency and transmission efficiency, so that the first charge and discharge specific capacity of the prepared negative electrode material is higher, and then the surface defects of the material are modified by vapor deposition, so that the first coulomb efficiency can be significantly improved. It can be seen from the data in Table 1 that the first charge and discharge specific capacity and the first coulomb efficiency of the embodiment are better than those of the comparative example as a whole. The first charge specific capacity in this application can reach 340mAh·g -1 Above, the first Coulomb efficiency can reach between 84% and 90%, which is at a relatively high level.
[0151] Table 1
[0152]
[0153] In Comparative Example 1, since the hard carbon precursor is not subjected to the first heat treatment, the specific surface area of the hard carbon precursor material cannot be increased to expose more active sites, the nitrogen source compound cannot react with the oxygen-containing functional groups to undergo a good chemical crosslinking reaction, and the interlayer spacing d of the graphite carbon layer is 002 It is difficult to expand effectively, so the sodium ion adsorption efficiency and transmission efficiency are low, resulting in low initial charge and discharge specific capacity and initial coulombic efficiency. In Comparative Example 2, since no carbon coating treatment was performed, the surface defects of the material could not be effectively modified, and the specific surface area was large, resulting in significantly lower initial charge specific capacity and initial coulombic efficiency. In Comparative Example 3, since no cross-linking polymerization reaction of the nitrogen source compound was performed on the second precursor, that is, no nitrogen atom was doped on the first precursor, the interlayer spacing d of the graphite carbon layer was 002 It is too small to store sodium ions in the micropores inside the material from the intercalation layer. At the same time, the lack of cross-linking between nitrogen atoms and oxygen-containing functional groups in the carbon layer makes it impossible to effectively absorb and store sodium ions. Therefore, the initial charge-discharge capacity and initial coulombic efficiency are low. It can be seen that in the preparation of the negative electrode material of the present application, the hard carbon precursor is subjected to a first heat treatment, the first precursor, the nitrogen source compound, the cross-linking agent and the initiator are added to the solvent for a cross-linking polymerization reaction, and the second precursor is subjected to a carbon coating treatment. The lack of any step cannot maintain a high initial charge-discharge capacity and effectively improve the initial coulombic efficiency.
[0154] The present application firstly selects a hard carbon precursor that has abundant oxygen-containing functional groups (such as carboxyl and hydroxyl groups). During the low-temperature pretreatment (first heat treatment), the excess ash, volatile matter and organic and inorganic small molecules in the hard carbon precursor material escape from the surface of the material, increasing the surface defects of the first precursor, and adding a large number of openings in the material to construct a porous structure, increase the pore volume, and significantly increase the specific surface area of the first precursor. Secondly, the nitrogen source compound forms a positively charged free radical under the action of an initiator, and chemically cross-links with the carboxyl and hydroxyl functional groups at the defects of the first precursor and between the intercalations, so that the nitrogen source compound can be precisely doped therein to form an active ion (Na+ , Li + ) provides a large number of adsorption active sites, expands the distance between graphite layers, thereby effectively increasing the diffusion rate of active ions and improving the electrochemical performance of negative electrode materials. Furthermore, chemical vapor deposition is used to crack gas-phase small molecule alkane or olefin compounds so that they can be evenly deposited on the second precursor interface, modifying the surface defects of the material and improving the first coulombic efficiency.
[0155] The microscopic morphology of the negative electrode material prepared in Example 1 is as follows: Figure 2 shown. Figure 3 TEM image of the negative electrode material prepared in Example 1. Figure 3 It can be seen that the graphite interlayer spacing in the negative electrode material is above 3.9Å, and the larger one can reach 3.98Å. The average graphite interlayer spacing of the negative electrode material prepared in Example 1 is 0.394nm, i.e. 3.94Å. The graphite interlayer spacing of conventional hard carbon materials is around 3.7Å. In the negative electrode material prepared in this application, the graphite interlayer spacing is significantly increased, which can effectively improve the active ion diffusion rate and the ability to embed active ions in the intercalation layer, thereby improving the capacity of the negative electrode material. In addition, by Figure 3 It can be seen that the negative electrode material contains a large number of short-range ordered graphite-like microcrystals entangled and stacked microporous structures. This structure can provide a large amount of storage space for active ions, thereby increasing the capacity of the battery, which is consistent with the above-mentioned electrochemical performance test results.
[0156] Figure 4 The charge and discharge curve of the battery made of the negative electrode material obtained in Example 1, Figures 5 to 7 The charge and discharge curves of the batteries made of the negative electrode materials obtained in Comparative Examples 1 to 3 are shown respectively.
[0157] In the charge-discharge curve, the gram capacity in the slope area (>0.1V) of the charge curve is mainly related to the adsorption of active ions on the surface of the negative electrode material, and the gram capacity in the platform area (0.1V-0V) of the charge curve is mainly related to the filling of active ions in the micropores inside the negative electrode material and the embedding between carbon layers. Therefore, the gram capacity ratio in the platform area of the charge curve can reflect the ratio of micropore volume in the negative electrode material, that is, the size of the storage space that can be provided for active ions in the negative electrode material. Figures 4 to 7The test charge and discharge curves show that the platform area gram capacity of the negative electrode material charging curve prepared in Example 1 accounts for more than 70%, and the platform area gram capacity of the negative electrode material charging curve prepared in Comparative Examples 1 to 3 accounts for 54%, 61%, and 48%, respectively, which are significantly lower than that in Example 1. This shows that the present application first constructs a better porous structure in the hard carbon material through low-temperature heat treatment, and secondly effectively increases the graphite layer spacing through sufficient doping of nitrogen source compounds, and further better modifies the surface defects of the material through gas phase coating, so that the prepared negative electrode material can provide a larger storage space for active ions, which is convenient for the embedding and transmission of active ions, thereby effectively improving the capacity performance of the negative electrode material.
[0158] It should be noted that the negative electrode material embodiments, negative electrode material preparation method embodiments, negative electrode plate embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in each embodiment can be arbitrarily combined without conflict.
[0159] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: The method comprises the following steps: S1: Under a first inert gas atmosphere, performing a first heat treatment on a hard carbon precursor to obtain a first precursor, wherein the temperature of the first heat treatment is 200° C. to 600° C., and the hard carbon precursor includes oxygen-containing functional groups, and the oxygen-containing functional groups include carboxyl groups and / or hydroxyl groups; S2: adding the first precursor, the nitrogen source compound, the crosslinking agent and the initiator into a solvent to carry out a crosslinking polymerization reaction, filtering, washing and drying to obtain a second precursor; the mass ratio of the first precursor, the nitrogen source compound, the crosslinking agent and the initiator is 100: (0.1-5): (0.1-2): (0.1-2), and the temperature of the crosslinking polymerization reaction is 80°C-150°C; S3: performing carbon coating treatment on the second precursor to obtain the negative electrode material.
2. The method for preparing the negative electrode material according to claim 1, characterized in that: Step S1 satisfies at least one of the following characteristics (1) to (4): (1) The first inert gas includes at least one of argon, nitrogen, and helium; (2) The hard carbon precursor includes at least one of sodium alginate, starch, β-cyclodextrin, glucose, fructose, cellulose, and lignin; (3) The heating rate of the first heat treatment is 0.1°C / min~10°C / min, and the holding time is 0.5h~6h; (4) The specific surface area of the first precursor is 100 m 2 / g~300m 2 / g.
3. The method for preparing the negative electrode material according to claim 1, characterized in that: Step S2 satisfies at least one of the following characteristics (1) to (4): (1) The nitrogen source compound includes at least one of acrylamide, urea, hydrazine hydrate, pyrrole nitrogen, pyridine nitrogen, and acrylonitrile; (2) The cross-linking agent includes at least one of tetramethylethylenediamine, N,N'-methylenebisacrylamide, and ethylene glycol dimethacrylate; (3) The initiator includes at least one of azobisisobutyl cyanide, ammonium persulfate-sodium bisulfite, azobisisobutyl cyanide, and hydrogen peroxide; (4) The solvent includes at least one of water, ethanol, acetone, toluene, ether, N,N'-dimethylformamide, and ethylene glycol monomethyl ether.
4. The method for preparing the negative electrode material according to claim 1, characterized in that: The carbon coating process in step S3 includes: A carbon source gas is introduced to perform gas phase coating on the second precursor; the gas phase coating has at least one of the following characteristics: a) the gas phase deposition temperature is 600°C~1000°C; b) the deposition time is 2h~5h; c) the introduction flow rate of the carbon source gas is 2L / min~10L / min; d) the carbon source gas includes alkane and / or alkene compounds.
5. The method for preparing a negative electrode material according to any one of claims 1 to 4, characterized in that: Before step S1, the method further includes: The hard carbon precursor is purified by an acid solution, then washed with water to a pH of 5-8, and filtered and dried to obtain a purified hard carbon precursor; the purification process has at least one of the following characteristics: a) the mass fraction of the acid solution is 1%-18%; b) the acid solution includes at least one of sulfuric acid, nitric acid, hydrofluoric acid, and hydrochloric acid; c) the ash content of the purified hard carbon precursor is ≤2%; d) the median particle size Dv50 of the purified hard carbon precursor is 2μm-6μm.
6. The method for preparing a negative electrode material according to any one of claims 1 to 4, characterized in that: The method further comprises: Under a second inert gas atmosphere, the negative electrode material is subjected to a second heat treatment, and the second heat treatment has at least one of the following characteristics: a) the temperature of the second heat treatment is 1000°C~1600°C; b) the insulation time is 2h~5h; c) the heating rate is 1°C / min~5°C / min; d) the second inert gas includes at least one of argon, nitrogen, and helium.
7. The method for preparing the negative electrode material according to claim 6, characterized in that: The method further comprises: After the second heat treatment, cooling and sieving are performed; the negative electrode material after sieving has at least one of the following characteristics: a) ash content ≤ 0.05%; b) median particle size Dv50 is 4 μm~8 μm; c) specific surface area is 5m 2 / g~15m 2 / g.
8. A negative electrode material, characterized in that The negative electrode material is prepared by the method for preparing the negative electrode material according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The negative electrode plate includes the negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or includes the negative electrode material according to claim 8.
10. A battery, characterized in that: Including the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Composite hard carbon cathode material of lithium ion battery and preparation method thereof
CN101887966A
Preparation of hard carbon negative electrode material for lithium ion power battery and modification method therefor
WO2017121069A1
Hard carbon negative electrode material for sodium-ion battery and preparation method therefor
WO2023109660A1
Negative electrode active material and preparation method therefor, negative electrode plate containing same, electrochemical device, and electronic device
WO2023184106A1
